Carsharing - Utopia or Real Gamechanger? - Conceptualising The Potential of Carsharing for Tackling Carbon Emissions - Andreas Collet; Philipp Scharfenberger (Marketing Review St.Gallen, 2023)
This conceptual paper addresses the different levers of both carsharing providers and their customers regarding the reduction of greenhouse gas emissions in the mobility sector. The various findings show that the main lever, besides the electrification of the vehicle fleet, is the integration of carsharing models into public transportation.
Keywords: 650